A dispositional approach to psychological climate: relationships between interpersonal harmony motives and psychological climate for communication safety - Wang, Jie; Leung, Kwok; Zhou, Fan (Sage Publications, 2014)
This study examined the dispositional antecedents of a climate at the individual level, psychological climate for communication safety. The impact of two interpersonal harmony motives, harmony enhancement and disintegration avoidance, on psychological climate for communication safety, innovative performance and the moderated mediated processes associated with job autonomy were examined in a survey study in China. Results showed that harmony enhancement was positively related to innovative performance through psychological climate for communication safety. Moreover, job autonomy moderated the relationship between harmony motives and psychological climate for communication safety. Harmony enhancement was more strongly associated with psychological climate for communication safety when job autonomy was low. The relationship between disintegration avoidance and psychological climate for communication safety was positive when job autonomy was high, but negative when job autonomy was low. Conditional indirect effects consistent with these interaction effects were also found.